2016
DOI: 10.1016/j.ccell.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

ERK Activation Globally Downregulates miRNAs through Phosphorylating Exportin-5

Abstract: SUMMARY MicroRNAs (miRNA) are mostly downregulated in cancer. However, the mechanism underlying this phenomenon and the precise consequence in tumorigenesis remain obscure. Here we show that ERK suppresses pre-miRNA export from the nucleus through phosphorylation of exportin-5 (XPO5) at T345/S416/S497. After phosphorylation by ERK, conformation of XPO5 is altered by prolyl isomerase Pin1, resulting in reduction of pre-miRNA loading. In liver cancer, the ERK-mediated XPO5 suppression reduces miR-122, increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
115
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 56 publications
3
115
0
4
Order By: Relevance
“…Deletion of miR‐122 increases the tumor incidence in mice, while injection of miR‐122 mimic results in ∼50% growth suppression of HCC xenografts, suggesting a potential miRNA‐based therapy for HCC . Recently, we revealed that Pin1 down‐regulates miRNA biogenesis by alternating the conformation of pXPO5 and promotes HCC development, indicating that enhancing miRNA biogenesis by inhibiting Pin1 is a promising strategy to treat HCC. In this study, we found that Pin1 inhibitor API‐1 activated the biogenesis of anticancer miRNAs and suppressed in vitro and in vivo HCC cell growth (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deletion of miR‐122 increases the tumor incidence in mice, while injection of miR‐122 mimic results in ∼50% growth suppression of HCC xenografts, suggesting a potential miRNA‐based therapy for HCC . Recently, we revealed that Pin1 down‐regulates miRNA biogenesis by alternating the conformation of pXPO5 and promotes HCC development, indicating that enhancing miRNA biogenesis by inhibiting Pin1 is a promising strategy to treat HCC. In this study, we found that Pin1 inhibitor API‐1 activated the biogenesis of anticancer miRNAs and suppressed in vitro and in vivo HCC cell growth (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In the posttranscriptional regulation of miRNA biogenesis by Pin1/XPO5/pre‐miRNA axis, Pin1 function depends on the phosphorylation level of XPO5. Increased XPO5 phosphorylation facilitates the Pin1‐mediated miRNA down‐regulation in HCC . However, with the inhibition of Pin1, XPO5 is active to export pre‐miRNA from nucleus to cytoplasm, even though XPO5 is highly phosphorylated (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that the down-regulation of miR-140-5p might also promote tumor growth and metastasis of many other cancers by directly increasing Pin1 expression to activate multiple cancer-driving pathways. Notably, Pin1 overexpression has been shown to reduce pre-miRNA export from the nucleus, resulting in global downregulation of miRNAs in liver cancer33. Therefore, the deregulation of the miR-140-5p/Pin1 interaction may represent an aggressive molecular lesion in cancer development by resulting in global reduction of miRNA and activation of numerous cancer-driving pathways, offering novel therapeutic targets not only for HCC, but also for other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Pin1 is overexpressed in more than 70% human HCC patients2930 and Pin1 overexpression transforms normal liver cells26, where Pin1 genetic knockdown inhibits HCC tumor growth induced by HBx31 and multiple Pin1-dependent cancer pathways in HCC32. Moreover, Pin1 overexpression results in global downregulation of microRNAs (miRNAs) in HCC33. However, although Pin1 has been shown to be regulated by multiple mechanisms notably in breast cancer283435, little is known so far about the molecular mechanism of Pin1 overexpression in HCC.…”
mentioning
confidence: 99%